2019
DOI: 10.4314/sajas.v48i6.18
|View full text |Cite
|
Sign up to set email alerts
|

Supranutritional supplementation of vitamin E influences mitochondrial proteome profile of post-mortem <i>longissimus lumborum</i> from feedlot heifers

Abstract: Supplementation of vitamin E improves beef colour stability by minimizing lipid oxidation-induced myoglobin oxidation. Mitochondria affect myoglobin redox stability, and dietary vitamin E influences mitochondrial functionality in skeletal muscles. Nonetheless, the influence of vitamin E on the mitochondrial proteome of beef skeletal muscles has yet to be investigated. Therefore, the objective of this study was to examine the effect of dietary vitamin E on mitochondrial proteome of post-mortem beef longissimus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…CKM was also reported in other proteomic studies to play an important role in beef colour (Mahmood et al 2018;Nair et al 2018a;Zhai et al 2018). This protein has been described as a biomarker of most quality traits of meat including tenderness, drip loss, water-holding capacity and pH decline (Ouali et al 2013).…”
Section: Ckm a Positive Biomarker In Colour-stable Beef Musclesmentioning
confidence: 73%
See 1 more Smart Citation
“…CKM was also reported in other proteomic studies to play an important role in beef colour (Mahmood et al 2018;Nair et al 2018a;Zhai et al 2018). This protein has been described as a biomarker of most quality traits of meat including tenderness, drip loss, water-holding capacity and pH decline (Ouali et al 2013).…”
Section: Ckm a Positive Biomarker In Colour-stable Beef Musclesmentioning
confidence: 73%
“…Other colour parameters reported in some studies were; MRA, Metmyoglobin Reducing Activity, OCR, Oxygen Consumption Rate and R630/580, surface colour stability. Ten studies that reported protein abundances, but not correlation analyses, or comparisons of muscle proteome abundance with ageing time colour traits or proteomics of dark cutting, were not included in the database (Yu et al 2017b;Mahmood et al 2018;Nair et al 2018b;Zhai et al 2018;Zhang et al 2018;Hughes et al 2019;Kim et al 2019;Wu et al 2019;Wu et al 2020). However, the results from these studies are cited and discussed where useful in this review.…”
Section: Database Descriptionmentioning
confidence: 99%
“…The relative volume of each spot was normalized as a percentage of the total volume of all the spots detected on the gel (Joseph et al, 2012). For each spot in a given sample, spot quantity values in duplicate gels were averaged for statistical analysis (Nair et al, 2018a;Zhai et al, 2018). A spot was considered to be differentially abundant when it demonstrated 1.5-fold intensity difference between the treatments associated with P < 0.05 in a pairwise Student t test.…”
Section: Gel Image Analysismentioning
confidence: 99%
“…OGDHC was more abundant in mitochondria from LL3 steaks than in mitochondria from LL6 steaks. OGDHC mediates the decarboxylation of alphaketoglutarate; it catalyzes the conversion of 2-oxoglutarate to succinyl-CoA and CO 2 and generates NADH (Qi et al, 2011;Zhai et al, 2018). In postmortem skeletal muscles, NADH regeneration is closely associated with both enzymatic and nonenzymatic metmyoglobin reduction (Saleh and Watts, 1968;Renerre and Labas, 1987;Echevarne et al, 1990;Mancini and Hunt, 2005;Kim et al, 2006).…”
Section: Retail Display Influences Mitochondrial Proteome Profile Of ...mentioning
confidence: 99%
“…This, in turn, could explain the overabundance of this protein in C-60 steaks compared with C-71 counterparts. Creatine kinase S-type is a mitochondrial creatine kinase isoenzyme, which reversibly catalyzes the interconversion of adenosine diphosphate (ADP) and phosphocreatine to adenosine triphosphate (ATP) and creatine, contributing to the ATP-ADP equilibrium in postmortem skeletal muscles (Gao et al, 2016;Zhai et al, 2018). Creatine kinase S-type has rarely been previously reported in meat research.…”
Section: Enzymes Involved In Energy Metabolismmentioning
confidence: 99%